Financial Reporting Analysis of Micro, Small and Medium Enterprise (MSMEs): Study on Tenggo Coffee - Dini Aylulliyah; Naz’aina Naz’aina (LPPM Universitas Malikussaleh, 2022)
This research aims to analyze financial recording for micro, small and medium enterprises (MSMEs). Data was obtained through interviews and observations of MSME actors. The data analysis technique uses qualitative descriptive analysis. The research results show that Tenggo Coffee have not carried out financial recording and reporting. Furthermore, the majority of MSMEs have never attended financial management training, especially financial reporting. Therefore, MSME actors want training and assistance in financial reporting by the government or other institutions. This information is important for local governments and related agencies in the context of counseling and assisting business management in the future.